Religious Books in the Reconstructed Fond in the Library of the Orenburg Theological Seminary - A. V. Bezpalova (Библиосфера, 2022)
The article is devoted to the library of the Orenburg Theological Seminary, which was lost in 1918. It was based on the books of spiritual and religious content. The purpose of the library reconstruction is to create its approximate catalog at the time of the seminary closure. The article describes only that sections of the catalog that reflect physically preserved books: Holy Scripture, Dogmatic Theology, Homiletics, Pastoral Theology, Moral Theology, Asceticism, Ecumenism, Christian apologetics, Schismatic studies, history of non-Christian religions, history of the Russian Orthodox Church, etc. Only 35 copies have been survived to this day. All of them are monuments of book culture and give an idea of both the representativeness of the lost library itself and the preparation of clergymen for missionary activity in the Orenburg Orthodox Diocese.